Towards A Framework For ICT-Enabled Materials Management In Complex Projects - Kasim, N. B. (Journal of Techno-Social, 2010)
This paper describes a research project, aimed at developing a system to integrate RFID-based materials management with resources modelling in project management to improve on-site materials tracking and inventory management processes. In order to develop the system, a comprehensive literature review and exploratory case studies were conducted to investigate current practices, problems, implementation of ICT and potential use of emerging technologies (such as RFID and wireless technologies) in overcoming the logistical difficulties associated with materials management. An initial assessment revealed that there is a potential to improve the tracking and management of materials using modern ICT, thus will enhance the operational efficiency of the project delivery process. Moreover, sophisticated technologies such as wireless systems and tagging are not generally used to overcome human error in materials identification and the space constraints inherent in many projects. This paper concludes the finding from case studies for developing a real-time materials tracking framework to support construction professional in handling materials more effectively.